Desenvolvimento de uma técnica óptica para caracterização da presença de crosta superficial do solo - Barreto, Bianca Batista (2016)
The expansion of the agricultural frontier and the recurrent disturbances caused by the production practices are responsible for the exposure and the degradation factors for the soil in its physical, chemical and biological properties. The formation of superficial crusts in the soil may compromise the crop, given the damages to soil structure, water infiltration and modification of roughness and porosity, increasing surface drainage and, consequently, erosion. In specific cases, it is possible to have superficial crusts as a positive factor for agricultural practice, thus, the monitoring of their occurrence is relevant. Optical techniques, such as laser and image processing, are potential tools for non-destructive superficial analysis of the soil. This work aimed to develop a non-destructive, low cost, portable and robust technique for characterizing the soil regarding the presence of superficial crust. Images of samples with and without superficial crusts were illuminated, registered, processed identifying the parameters that can be linked to the crust. The results showed that it is possible to use the optic technique as method for differentiating superficial crust of the soil in a non destructive manner.